The Wrongfully Convicted Deserve Acquittals Not Prosecutorial Stays - Roach, Kent (The Canadian Bar Review, 2024)
Between 2006 to 2008, no less than three public inquiries recommended that, absent a reasonable likelihood of re-prosecution, prosecutors should allow the wrongfully convicted to be acquitted and not be subject to prosecutorial stays. Prosecutorial stays are an exercise of prosecutorial discretion under. 579 of the Criminal Code that can only be challenged with evidence of flagrant impropriety. They do not provide protection against double jeopardy. They can amount to a third “legal limbo” verdict between guilty and not guilty. Only two prosecutorial services in Canada have adopted the three inquiry recommendations in their guidelines or deskbooks. This failure has real world consequences: namely at least five cases involving seven accused in four different provinces since 2016 where convictions were overturned because of new evidence relevant to guilt or innocence only to be the subject of a prosecutorial stay which deprived the previously convicted person of a verdict on the merits. In addition to being at odds with the three inquiry recommendations, such uses of prosecutorial stays promote continued suspicion of the wrongfully convicted and create two classes of the wrongfully convicted: those who are acquitted and those who only receive a prosecutorial stay.